The Activity Test of Aedes Aegypti Larvacid from The Combination of Lemongrass Oil with Pineapple Extract - Misde yola; Joko Sulistiyo (Politeknik Kesehatan Kemenkes Jakarta II, 2020)
Pineapple plants contain a very important enzyme called bromeilin. Bromeilin is one type of protein enzymatic. The benefits of bromelin are as meat plasters which can damage the cell walls through enzymatic reactions. This research was conducted to determine the activity of pineapple extract and lemongrass oil extract as aedes aegypti mosquito larvae killer Instar III. It has been done research on the activity test of pineapple extract to death of larvae of aedes aegypti instar 3 mosquito. Pineapple extract is made with concentration from 1to 10 ppm. Each concentration was tested in 25 larvae of aedes aegypti for 24 hours to observe the killing activity. After 24 hours the number of dead aedes aegypti larvae was count. Then the data was determined by parametric test Kruskal-Wallis. Results obtained: there was a significant difference in the presentation of the death of aedes aegypti intar III larvae at various concentrations. The optimal combination of pineapple extract and lemongrass oil was at 4 ppm concentration (p = 0.007).